IDENTIFICATION OF HORIZONTAL ERRORS IN BATHYMETRIC SURVEYS - Yusuf Faisol, Deki
Bathymetric survey is a measurement activity that aims to determine the depth of the waters so that it can describe the shape of the bottom surface of the waters. In the bathymetric survey there are several systems used from mechanics, optics, and acoustics. Generally bathymetric surveys use echosounder in determining the depth and positioning the depth point using the Global Navigation Satellite System (GNSS). To obtain good data quality from bathymetric surveys, measurement errors need to be considered carefully. This study aims to identify the source of the horizontal error and determine the magnitude of the horizontal error from the bathymetric survey measurement results. The sources of errors that cause measurement errors are natural errors, tool errors, and human errors. In this study, the method used is a study of literature obtained from research journals, books, reports, agreements that are considered official and other written sources as the main object. The results of the analysis of this study are (1) identification of the horizontal error source in the bathymetric survey and (2) quantification of the error value. The horizontal error quantification consists of depth point position error, transducer position error, time delay error, and ship direction error. From the results of quantification carried out using simulation data, it can be seen that the measurement error is ±1.75 m and based on the International Hydrographic Organization (IHO) S-44 the measurement falls into the criteria of order 1a.